Site-Specific Editing of the Plasmodium falciparum Genome Using Engineered Zinc-Finger Nucleases - Straimer, Judith (2012)
Malaria afflicts over 200 million people worldwide and its most lethal etiologic agent, Plasmodium falciparum, is evolving to resist even the latest-generation therapeutics. Efficient tools for genome-directed investigations of P. falciparum pathogenesis, including drug resistance mechanisms, are clearly required. Here we report rapid and targeted genetic engineering of this parasite, using zinc-finger nucleases (ZFNs) that produce a double-strand break in a user-defined locus and trigger homology-directed repair. Targeting an integrated egfp locus, we obtained gene deletion parasites with unprecedented speed (two weeks), both with and without direct selection. ZFNs engineered against the endogenous parasite gene pfcrt, responsible for chloroquine treatment escape, rapidly produced parasites that carried either an allelic replacement or a panel of specified point mutations. The efficiency, versatility and precision of this method will enable a diverse array of genome editing approaches to interrogate this human pathogen.